1994
DOI: 10.1002/chir.530060104
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective inhibitory effect of nicardipine on the hepatic clearance of propranolol in man

Abstract: The influence of a single oral dose of 30 mg nicardipine on the pharmacokinetics of (R)- and (S)-propranolol, given orally as rac-propranolol 80 mg, was studied in 12 healthy volunteers. The plasma concentrations were higher for the (S)-enantiomer than for the (R)-enantiomer. The Cl(o) and the Cl'intr of (S)-propranolol were significantly lower than the Cl(o) and Cl'intr of (R)-propranolol. The unbound fraction of (R)-propranolol was significantly higher than that of (S)-propranolol. Coadministration of nicard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…In maternal serum there was a small but significant difference in binding between the propranolol enantiomers, as reported previously in non-pregnant subjects [4,6] …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In maternal serum there was a small but significant difference in binding between the propranolol enantiomers, as reported previously in non-pregnant subjects [4,6] …”
Section: Discussionsupporting
confidence: 83%
“…It is not known to what extent binding in foetal serum is enantioselective. Therefore we have measured the binding of the isomers of propranolol and verapamil in pairs of maternal and foetal serum samples obtained at delivery; both drugs are bound to AAG and show enantioselective serum binding in adults [4][5][6]. We also determined whether, based on the foetal/maternal AAG concentration ratio, foetal binding of the enantiomers can be predicted from maternal binding data [1].…”
Section: Introduction Methodsmentioning
confidence: 99%
“…This may be due to an enantioselective influence of the interacting drug on not only hepatic, but perhaps also gastrointestinal availability of the enantiomers. The effects of inhibitory interactions at the level of metabolism are generally more apparent on the oral clearance of the ðþÞ enantiomer of propranolol than the ðÀÞ enantiomer, leading to significant increases in the ðþÞ : ðÀÞ ratio in plasma and/or serum [81][82][83][84]. Induction also can lead to stereoselectivity in plasma concentrations, as is demonstrated for verapamil after coadministration of rifampin.…”
Section: Stereospecific Drug Interactionsmentioning
confidence: 99%
“…Not only CYP3A4 and CYP2D6, but essentially all CYP forms investigated in the present study were also inhibited by nicardipine in vitro as reported by Katoh et al 19) This may account for a reported in vivo pharmacokinetic interaction between nicardipine and other drugs such as propranolol. 20,21) Considering the mechanism of inhibition, a competitive inhibition of these CYPs was suggested in the present study (data not shown). In conclusion, nicardipine can be metabolized mainly by human CYP2C8, CYP2D6 and CYP3A4, whereas it could be a relatively potent competitive inhibitor of these CYPs.…”
Section: Discussionmentioning
confidence: 59%